A Fuzzy PID Controller for Induction Heating Systems with LLC Voltage Source Inverter - Arijit Chakrabarti; Pradip Kumar Sadhu; Avijit Chakraborty; Palash Pal (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
The Proportional-Integral-Derivative (PID) controller is the most popular control strategy in the process industry. The popularity can be attributed to its simplicity, better control performance and excellent robustness to uncertainties that is found through the research work on such controllers so far. This paper presents the design and tuning of a PID controller using Fuzzy logic for industrial induction heating systems with LLC voltage source inverter for controlling the induction heating power. The paper also compares the performance of the Fuzzy PID controller with that of a conventional PID controller for the same system. The system and the controllers are simulated in MATLAB/SIMULINK. The results show the effectiveness and superiority of the proposed Fuzzy PID controller.